2000
DOI: 10.1038/35008075
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric redirection of flow through the heart

Abstract: Through cardiac looping during embryonic development, paths of flow through the mature heart have direction changes and asymmetries whose topology and functional significance remain relatively unexplored. Here we show, using magnetic resonance velocity mapping, the asymmetric redirection of streaming blood in atrial and ventricular cavities of the adult human heart, with sinuous, chirally asymmetric paths of flow through the whole. On the basis of mapped flow fields and drawings that illustrate spatial relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
500
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 623 publications
(565 citation statements)
references
References 20 publications
(16 reference statements)
53
500
1
1
Order By: Relevance
“…It showed the well-defined vortex ring-like structure of the vorticity field, (see Fig. 1 for an exemplary case), in qualitative agreement with a previous in vivo study 51 and a following mixed numerical and experimental one. 22 A further study analyzed the influence of the eccentric position of mitral orifice with respect to the LV geometry, 73 suggesting that the physiological arrangement corresponds to the minimal kinetic energy dissipation within the LV.…”
Section: Theoretical Modelssupporting
confidence: 89%
“…It showed the well-defined vortex ring-like structure of the vorticity field, (see Fig. 1 for an exemplary case), in qualitative agreement with a previous in vivo study 51 and a following mixed numerical and experimental one. 22 A further study analyzed the influence of the eccentric position of mitral orifice with respect to the LV geometry, 73 suggesting that the physiological arrangement corresponds to the minimal kinetic energy dissipation within the LV.…”
Section: Theoretical Modelssupporting
confidence: 89%
“…The phenomenological organization of the LV flow in the normal subjects is in agreement with those reported in the literature. It has been confirmed that normal diastolic filling is characterized by the presence of a 3D vorticity structure that develops into a dominant asymmetric vortex, a relatively smooth wheel-like motion over the whole cavity, which is associated with flow redirection toward the aorta (Kilner et al, 2000;Pedrizzetti and Domenichini, 2005). This global picture significantly changes in the context of DCM.…”
Section: Energetic Flow Aspectsmentioning
confidence: 83%
“…Phase-contrast velocity mapping with magnetic resonance imaging (PC-MRI) has become an important tool for quantifying and visualizing blood flow patterns in the human body (1)(2)(3)(4).…”
mentioning
confidence: 99%